Promoting Emotional Well-Being in Older Adults: Teaching Self-Regulation to Address Obsession and Depression - Maryam Mehrara; Neda Fatehi; Valeh Jalali (Iranian Evolutionary Educational Psychology Journal)
Objective: This investigation endeavors to elucidate the methodologies through which self-regulation can be imparted to older adults to enhance their acquisition of a foreign language while concurrently enabling them to navigate adverse emotional experiences. In particular, this study scrutinizes the phenomena of obsession and depression. Furthermore, Alzheimer's disease represents a considerable burden for the older population, compounding the inherent difficulties associated with aging and detrimentally influencing their overall quality of life. Consequently, we aim to propose a framework that empowers elderly individuals to reclaim a semblance of control over their obsessive thoughts and depressive states. Methods: The research encompasses 40 Iranian participants who are 65 years of age or older, in alignment with the World Health Organization's classification of elderly individuals. These participants were recruited employing a convenience sampling method. The study utilizes a quasi-experimental design featuring pre-test and post-test assessments alongside a control group. Results: The results indicate that the instruction of the English language exerts a notable effect in mitigating obsessive thoughts and depressive symptoms among adults diagnosed with Alzheimer's disease. Conclusions: This research bears significant implications for elderly individuals in the initial phases of Alzheimer's, their caregiving relatives, psychologists addressing the emotional difficulties faced by older adults, and policymakers involved in the domain of language education.